The Use of Secondary Skin Materials for Natural Lighting in Hotels Resorts - Siti Sarah Kamilah Irfan; Maria Immaculata Ririk Winandari; Sri Tundono (Center for Scientific Publication, 2023)
Natural lighting is one aspect of ecological architecture to reduce energy use by utilizing sunlight as the main lighting. However, direct and excessive sunlight decreases the comfort level of room users because it can increase the room temperature and interfere with visualization. So it takes control of the distribution of sunlight into the room. In addition, the issue of environmental damage has become hot news among the community today, especially in the property sector, such as using materials that can damage the surrounding environment. Efforts to regulate the entry of sunlight into the room but not harm the surrounding environment, one of which is the application of second skin that utilizes environmentally friendly materials. This paper aims to determine the form and material of secondary skin that is environmentally friendly and suitable for use in resort hotels. This research uses a qualitative comparative method based on three objects in the form of secondary skin in the hotel resort building: Ananta Legian Hotel Bali, EcoSuites (A Reed-Clad Hotel Greece), and Lenora Hotel Bandung with variables namely opening, shape, and shading. For three secondary skin material objects in the resort hotel building, namely Amnaya Resort Kuta, Four Points by Sheraton Bali, and Potato Heads Studio Hotel Bali with variables namely shape, material, and aesthetics. Based on the results of the study, it was found that there are two types of second skin openings that are applied to the hotel resort building, namely dead openings and sliding openings that are applied to adjust the shape with the dominance of the modified rectangular base shape and the shadow produced from the second skin itself adjusts to the function of the shaded space. Environmentally friendly materials used are made from nature, such as vegetation, wood, and roaster bricks that do not damage the surrounding environment, which are applied in a modified rectangular base shape and can improve the aesthetics of the building.